PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE (IOC) DALAM MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIIIa SMPN 2 LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI TAHUN PELAJARAN 2011/2012 - Yustini Yusuf; Arnentis '; Siski Yusika (Biogenesis, 2012)
This study aims to increase the activity and student learning outcomes biology class VIIIa SMPN 2 Logas Tanah Darat through the implementation of cooperative learning model of Type Inside Outside Circle (IOC). This research was classroom action research conducted in NovemberDecember 2011. Subjects were students in grade VIIIa SMPN 2 Logas Tanah Darat land totaling 24 students, consisting of 12 male students and 12 female students. The parameters in this study is, student activities, teacher activities and student learning outcomes. Student activities that increase of 86.01% (very good) on a cycle I increased to 96.35% (very good category) in the second cycle. And activities that teachers have increased from 94.45% (very good) on a cycle I to 100% (very good) in the second cycle. Absorptive capacity of students also increased, the cycle I with an average of 68.54% (category enough), the second cycle with an average of 75.20% (both categories). Thoroughness of student learning has increased with the percentage of completeness in the cycle I was 83.33% and 95.83% the second cycle. Appreciation group on the cycle I have 2 groups and 4 groups predicated predicated super great, whereas in the second cycle 5 and a great group predicated predicated super group. From the research results can be concluded that the application of cooperative learning model of Type Inside Outside Circle (IOC) can increase the activity and learning outcomes of students Biology class VIIIa SMPN 2 Logas Tanah Darat Lessons Year 2011/2012.Keywords: Activities, cooperative learning model type Inside Outside Circle (IOC), Learning Outcomes